(untitled) (Eurasian Journal of Philology Science and Education, 2019)
In this essay discusses artistic and stylistic features of Kazakh aphorisms. The proverbial genre of Kazakh aphorisms speaks about the artistic side effects of proverbs, sayings and Bata words. In additional, the use of regularly encountered stylistic methods of Kazakh aphorisms.Specific features of the various types of visualization, such as equation, change, representation, definition, symbolism, classification, exaggeration, which are widely used in Kazakh aphorisms, are represented by specific examples. The use of aphorisms in fiction does not only increase the livelihood and clarity of language,as well as the opportunity to enrich the lexical language of the language. In this article, it is emphasized in the article that Kazakh aphorisms have a prominent feature in enriching language lexicon. as well as the fact that in the Kazakh literature the complex problems of the Kazakh aphorism are not fully studied, this article defines the artisticstyle character and peculiarities of Kazakh aphorisms.